2015
DOI: 10.1371/journal.pone.0139506
|View full text |Cite
|
Sign up to set email alerts
|

Annexin A2 Acts as an Adhesion Molecule on the Endometrial Epithelium during Implantation in Mice

Abstract: To determine the function of Annexin A2 (Axna2) in mouse embryo implantation in vivo, experimental manipulation of Axna2 activities was performed in mouse endometrial tissue in vivo and in vitro. Histological examination of endometrial tissues was performed throughout the reproduction cycle and after steroid treatment. Embryo implantation was determined after blockage of the Axna2 activities by siRNA or anti-Axna2 antibody. The expression of Axna2 immunoreactivies in the endometrial luminal epithelium changed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 33 publications
0
19
0
Order By: Relevance
“…The study demonstrated that disruption of the maternal MTHFD1 gene damages fetal growth [ 86 ]. There are also ample studies that suggest ANXA2 is closely involved with embryo implantation and breast cancer, by acting as an adhesion molecule on the endometrium [ 87 , 88 , 89 ].…”
Section: Resultsmentioning
confidence: 99%
“…The study demonstrated that disruption of the maternal MTHFD1 gene damages fetal growth [ 86 ]. There are also ample studies that suggest ANXA2 is closely involved with embryo implantation and breast cancer, by acting as an adhesion molecule on the endometrium [ 87 , 88 , 89 ].…”
Section: Resultsmentioning
confidence: 99%
“…Annexin A1 knock-out female mice displayed numerous changes in early gestation, including increased sites of implantation, increased inflammatory reaction in the uterine fluid during implantation, reduced pre-and post-implantation losses and enhanced plasma progesterone [46]. Furthermore, ANXA2 was shown to be crucial for embryo adhesiveness to the endometrium, a critical step for implantation, in humans [47] and mice [48].…”
Section: Discussionmentioning
confidence: 99%
“…For example, annexin A1 and annexin A2 were reported to have a lesser expression in the chorioamnion and adjacent uterine caruncles for embryos with retarded development compared to embryos with normal development in the Italian Mediterranean River buffalo (Balestrieri et al, 2013; Strazzullo et al, 2014). Annexin A2 has been specifically implicated in embryo attachment in humans (Barone & Heisenberg, 2012; Garrido‐Gomez et al, 2012) and mice (Wang et al, 2015), while annexin A1 is involved with general cell adhesion (Horlacher et al, 2011). The studies in River Buffalo provided a clear demonstration of altered adhesion molecule function in a well‐characterized model of retarded embryonic development (Campanile, Neglia, & D'Occhio, 2016).…”
Section: Adhesion Molecules and Reproductionmentioning
confidence: 99%